Preventing depression and burnout in youth football - Nixdorf, I.; Beckmann, J.; Nixdorf, R. (Football Psychology - From Theory to Practice, 2019)
Until 2009 burnout and depression had been widely ignored in German football. In 2007 one of Germany`s greatest talents, Sebastian Deisler, ended his career aged 27 due to depression. But only after Germany`s national goalkeeper, Robert Enke, committed suicide in 2009, did official football declare that steps needed to be taken against burnout and depression. The following chapter will give you an overview of the definition, classifications, and theoretical assumptions about burnout and depression in elite athletes. We present current research and findings on sport specifics and football-related aspects (such as cognition and attitude, coping with stress and motivation) regarding these two syndromes, summarizing research and highlighting the most important aspects for young football athletes. The chapter continues with a section regarding practical implications. Here, a strong focus on prevention among young athletes is presented highlighting structural aspects and recommending content of prevention in youth football players. Concluding, the chapter will offer future research directions and deductions for applied sport psychologists active within football.